The male reproductive pattern of the Isan big-headed frog (Limnonectes isanensis, McLeod, Kelly, and Barley, 2012) at the Loei river in Loei province, Thailand - Tumkiratiwong, Panas; Suktongsa, Chatdanai (Agriculture and Natural Resources, 2025)
Importance of the work: Increasing research on the reproductive patterns of species threatened by capture for food leads to enhanced conservation data. Objectives: To monitored reproductive pattern of the male Isan big-headed frog, Limnonectes isanensis. Materials and Methods: Samples were collected monthly at the Loei river in Phu Luang district, Loei province, over a period of one year. The testes were excised for examination of annual morphological and histological changes, and blood was withdrawn via cardiac puncture for the determination of testosterone levels by radioimmunoassay (RIA). Results: The testes regressed from March to May, recrudesced from June to August and hypertrophied from September to February. Histological analysis of the seminiferous lobules exhibited that from May to August no luminal sperm bundles or free sperm were present, but abundant cystic spermatocytes were observed; from September to February, abundant sperm bundles and free sperm were observed, and fewer free sperm were present from March to April. The testosterone levels of male L. isanensis were low from March to August, gradually increased in September and October, and surged markedly from November until February of the following year. Main finding: The combined data on annual alterations in testicular morphology, spermatogenetic activity, and plasma testosterone levels demonstrate that the reproductive pattern of male L. isanensis follows an associated reproductive pattern.